A Highly Efficient Electrocatalyst Derived from Polyaniline@CNTs−SPS for the Oxygen Reduction Reaction1. Issue 1 (3rd November 2017) - Xu, Jingjing; Lu, Shiyao; Zhou, Han; Chen, Xu; Wang, Yuankun; Xiao, Chunhui; Ding, Shujiang
Abstract: It is of vital importance to develop novel, low‐cost, and high‐efficiency electrocatalysts for the oxygen reduction reaction (ORR), which have a considerable impact on electrochemical energy conversion and storage devices, such as fuel cells and metal−air batteries. In this work, we demonstrate highly active nitrogen‐doped carbons with uniform hierarchical structures through sulfonated polystyrene (SPS), regulating the distribution of the PANI covering on carbon nanotubes (CNTs), prepared by using a reliable and controllable route. The as‐prepared electrocatalyst shows outstanding activity towards the ORR in alkaline media, manifesting comparable or even better performance compared to commercial Pt/C. The optimized nitrogen‐doped CNTs exhibit an onset potential ( E onset ) of 0.94 V (vs. reversible hydrogen electrode (RHE)) and half‐wave potential ( E 1/2 ) of 0.83 V (vs. RHE) in 0.1 M KOH with superior stability, durability, and methanol tolerance, suggesting their promising applications in fuel cells and metal−air batteries. The significantly improved electrochemical properties demonstrate that the unique SPS layer anchoring on the surface of CNTs in the as‐designed PANI@CNTs‐SPS contributes to a uniform distribution of nitrogen sites throughout the catalyst. Abstract : Cats. got potential : A highly active nitrogen‐doped carbon is reported with uniform hierarchical structure through sulfonated polystyrene (SPS), which regulates the distribution of PANI covering the carbon nanotubes (CNTs). The electrocatalyst shows outstanding performance towards the oxygen reduction reaction in alkaline media. The optimized nitrogen‐doped CNTs exhibit an onset potential of 0.94 V (vs. RHE) and half‐wave potential of 0.83 V in 0.1 M KOH. Furthermore, the as‐prepared catalyst shows superior durability and methanol tolerance compared to the commercial Pt/C, suggesting promising applications in fuel cells and metal−air batteries.